Kinerja Usaha Mikro: Analisis Pengaruh Pembiayaan dan Karakteristik Kewirausahaan - Zulkarnain, Muhammad; Aurantia Marina; Mukarramah (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2024)
The research was conducted with the object being microenterprises in Ilir Barat District, Palembang City. Purpose of the research is to reveal wheather the performance of microenterprises is influenced by financing and entrepreneurial characteristics. The method used is quantitative. While primary data sourced from a research questionnaire with a sample of 98 respondents. The data analysis technique uses multiple linear regression equations. The results of the study obtained financing and entrepreneurial characteristic, both partially and simultaneously significant to the performance of microenterprises in Ilir Barat District, Palembang City. Financial institutions need to design financing schemes that are flexible and in accordance with the needs of micro businesses to support business growth.